Gambaran Kualitas Hidup pada Pasien Penderita Diabetes Melitus Tipe 2 di RSUD Cut Meutia Aceh Utara - Hilda Amalia; Yenny Sulisma (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2026)
Diabetes mellitus (DM) is a chronic metabolic disorder characterized by hyperglycemia resulting from impaired insulin secretion, insulin action, or both. Globally, DM continues to pose a growing health challenge, particularly type 2 DM, which is closely associated with insulin resistance. In this condition, body cells fail to respond effectively to insulin, so even though the pancreas initially produces sufficient or excessive amounts of insulin, its effectiveness gradually declines. Over time, pancreatic beta-cell function deteriorates, further exacerbating chronic hyperglycemia. This persistent condition may lead to long-term complications, including nephropathy, retinopathy, neuropathy, and cardiovascular diseases, through mechanisms such as oxidative stress, inflammation, and the formation of advanced glycation end products (AGEs). The prevalence of type 2 DM is expected to continue rising, including in Indonesia, highlighting the need for comprehensive management strategies. An important aspect of DM management is the assessment of health-related quality of life. Quality of life reflects an individual’s perception of their health status within social and cultural contexts. This can be evaluated using generic instruments such as the WHOQOL-BREF questionnaire. In this case report, the quality of life of a patient with type 2 DM was assessed using the WHOQOL-BREF to provide a comprehensive understanding of the disease’s impact on the patient’s daily life.